The effect of combination of active fraction Andrographis paniculata (Burm.f) Ness and Centella asiatica (i) Urban on the alpha glucocidase inhibitor and antioxidant activities - Arman Rusman; Agung Endro Nugroho; Suwidjiyo Pramono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
The Andrographis panicullata and Centella asistica extract have been reported that had a anti-diabetic effect. However, the specific mechanism and the effect combination of both were not yet reported. This study was purposed to determine the potency of extract, fractions and the combination of Andrographis panicullata (AP) and Centella asistica (CA) active fraction to inhibit alpha glucosidase enzymeand its ability to reduce DPPH radical.AP and CA were extracted using 50% ethanol then fractionated with solvents under different polarity levels. The inhibiting activity to alpha glucosidase enzyme and antioxidant activity of each fractions was tested. The most active fractions from AP and CA were then combined and re-tested for activity. The results result reported that both of AP and CA had inhibition of alpha glucosidase activity and antioxidant activity. Based on calculation combination index (CI) of of active fraction of AP and CA showing in alpha glucocidase activity had a antagonist action and antioxidant had a sinergic action. Therefore, combination of AP and CA not has not recomended for alpha glucocidase inhibitor but the combination has ability to reduce DPPH radical.